(untitled) (Rudarsko-geološko-naftni zbornik, 2018)
Vijenac quarry, near Tuzla in Bosnia-Herzegovina, is composed of carbonate rocks locally embedding tectonically disturbed siltite and sandstone with Mn-Fe concretions. The quarry itself represent a part of Dinaric overstep sequences (Pogari series) unconformably overlying ophiolite mélange and ophiolite trust-scheets. Petrographic, chemical and XRD analyses had shown that the concretions may be divided into two types: (i) Mn-rich concretions with ≈17% of Mn and compact texture and (ii) Mn-poor (≈8% of Mn) and porous texture. The amount of Ca, Mg, Fe and organic matter, as well as analysed microelements (Ni, Cr) in both concretion types are similar. According to petrographic and XRD analyses, concretions are composed of calcite, dolomite, hematite, todorkite and takenelite. Todorokite is characteristic for concretions formed by diagenetic growth. Petrographic study confirmed the development of concretions within three stages including two generations of calcite. The studied concretions are formed within consolidated sandstones inheriting their sedimentary textures - therefore a late diagenetic process is assumed.